Botswana : 2021 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Botswana. (IMF Staff Country Reports; Country Report ;, 2021)
Botswana entered the COVID-19 crisis with larger buffers than most countries, but significantly less than in the past. The country was contending with structural challenges, persistent negative external shocks and delays in adjustment that had already caused a significant weakening of international reserves coverage and the fiscal position amid high unemployment. The pandemic exacerbated these challenges causing a sharp GDP contraction, among the strongest in SSA and a widening in the current account deficit. Foreign exchange reserves dropped further, though still remaining well above adequate levels. The fiscal deficit widened significantly as the government sought to counter the economic impact of the COVID-19 crisis, and implemented a sizeable public wage increase agreed in 2019. The deficit was financed partially by drawing down on the Government Investment Account.